TRANSFORMATION OF 21ST CENTURY EDUCATION TO REALISE SUPERIOR HUMAN RESOURCES TOWARDS THE GOLDEN GENERATION - Lukmanul Hakim, Alif; Nisa, Rafika; Citrawati Lestari, Nana (CV. Lafadz Jaya, 2025)
The transformation of 21st century education is the main key in shaping superior human resources (HR) to realise the Golden Generation 2045. This research uses the literature review method to examine the concepts, challenges, and strategies of educational transformation in the digital era. The results show that 21st century education requires mastery of critical thinking skills, creativity, collaboration, communication, digital literacy, and character strengthening. However, the implementation of education transformation still faces challenges in the form of gaps in access, education quality, teacher readiness, and equitable distribution of technological infrastructure. To overcome these obstacles, a comprehensive strategy is needed in the form of equalising access to education, adaptive curriculum reform, improving teacher competence, and cross-sector collaboration. Adaptive, innovative and characterful education transformation is believed to be able to produce superior human resources who are ready to compete at the global level and contribute positively to the progress of the nation.